Effect of fast cooling on defects level, microstructure and magnetic properties of LiTiZn ferrite ceramics; Materials Chemistry and Physics; Vol. 227 - Malyshev A. V. Andrei Vladimirovich; Petrova A. B. Anna Borisovna; Sokolovsky A. N. Aleksey Nikolaevich; Surzhikov A. P. Anatoly Petrovich (2019, 2019)
Title screen